Progression From No AMD to Intermediate AMD as Influenced by Antioxidant Treatment and Genetic Risk: An Analysis of Data From the Age-Related Eye Disease Study Cataract Trial. (January 2017) - Awh, Carl C.; Zanke, Brent; Kustra, Rafal
Purpose: To investigate the impact of antioxidant treatment and genetic risk on the development of intermediate age-related macular degeneration (AMD) in patients without baseline AMD, using data from the Age-Related Eye Disease Study (AREDS) Cataract Trial. Methods: Genetic risk and antioxidant treatment were analyzed as independent and interacting risk factors for the development of intermediate AMD in 554 AREDS individuals for whom genotyping was available. Genetic risk was determined using an allele dosage model based on the total number of complement factor H and age-related maculopathy sensitivity 2 risk alleles. Results: Overall, 14% of patients developed intermediate AMD over approximately 8 years. The risk of developing intermediate AMD varied from 6.5% for patients with 0 risk alleles to 39% for those with 3 or 4 risk alleles ( P < .0001). Antioxidants had no impact on the development of intermediate AMD overall. However, antioxidant treatment had a significant impact on progression to intermediate AMD for patients with low or high genetic risk. Patients with 0 or 1 risk alleles had increased risk of progression to intermediate AMD (hazard ratio [HR] = 2.31, P = .017) if treated with antioxidants compared to placebo. Patients with 3 or 4 risk alleles had decreased risk of progression to intermediate AMD (HR = 0.27, P = .0008) if treated with antioxidants compared to placebo. Conclusion: On average, antioxidant treatment has no impact on the development of intermediate AMD in patients without AMD. However, antioxidant treatment may increase the risk of developing intermediate AMD in patients with low genetic risk and may reduce the risk of developing intermediate AMD in patients with high genetic risk. Since patients with high genetic risk have the greatest risk of progressing from intermediate to advanced AMD, genotype-directed antioxidant treatment of patients without AMD may ultimately lead to fewer cases of advanced AMD.